GALAXY GROUPS IN THE STRUCTURE OF THE UNIVERSE: OBSERVATIONAL AND STATISTICAL APPROACH (Universal International Scientific Journal, 2026)
In this paper, a catalog of 408 galaxy groups has been compiled. The number ofgalaxies in the groups ranges from 5 to 30. The physical parameters of the groups, such as rightascension, declination, luminosity, radial velocity, velocity dispersion, R magnitude, and B magnitude,are presented. The empirical relationship between each parameter has been statistically analyzed.
Keywords: galaxy groups; statistical analysis; empirical relationship